Barrier to Reproductive Health Services in Adolescents in Sukoharjo, Central Java - Maryatun Maryatun; Indarwati Indarwati; Endang Sri Wahyuni; Hermawati Hermawati (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Adolescent reproductive health information and services (KRR) are right, teenagers are helped to recognize themselves and matters relating to reproductive health. By having correct information, adolescents can equip themselves with behaviors and skills that can protect themselves from various reproductive health risks. This study aimed to analyze the factors that influence barriers to adolescent reproductive health services in schools.Subjects and Method: This was a cross sectional study was conducted at high schools in Sukoharjo, Central Java, from April to May 2018. The sample was 281 students selected by purposive sampling. The dependent variable is barriers to adolescent reproductive health services. The independent variables are attitude, information, distance of service, ability of service personnel, and utilization of health service facilities. Data were analyzed using Chi square.Results: The use of reproductive health services increased with knowledge of reproductive health (OR= 4.06; 95% CI= 1.8 to 9.2; p <0.001), positive attitude towards reproductive health (OR= 2.43; 95% CI= 1.2 to 5.1; p= 0.016), get information on KRR services (OR= 2.15; 95% CI= 1.05 to 4.4; p= 0.034), easy access to KRR services (OR= 2.2; 95% CI= 1.5 to 4.6; p= 0.033), the ability of officers in provide services (OR= 2.47; 95% CI= 1.2 to 5.2; p= 0.014), and utilization of health service facilities (OR= 1.5; 95% CI= 0.78 to 3.1; p= 0.21).Conclusion: Low service barriers are influenced by knowledge of reproductive health, positive attitudes towards reproductive health, obtaining information on KRR services, easy access to KRR services, the ability of officers to provide services, and utilization of health service facilities.Keywords: service barriers, adolescent reproductive healthCorrespondence: Maryatun. Study Program of Nursing, School of Health Sciences Aisyiyah, Surakarta. Email: tunmaryatun76@gmail.com.Journal of Health Policy and Management (2020), 5(1): 85-88https://doi.org/10.26911/thejhpm.2020.05.01.08